Loss of the Thermal Power in the Rolling Bearings at Different Speeds and Loads - Mhanna, Hazar (Latakia University Journal -Engineering Sciences Series, 2019)
Rolling bearing is considered to be one of the helpful elements that facilitate the function of different mechanisms, because it works as a mechanical tool that allows the rotational movement of the dynamic parts which have a relative movement within, and its main function is to reduce the friction between the shafts and the holes that holding them. A study of different types of the rolling bearings, according to the effect of speed and load on its performance, has done at this research experimentally by using a test apparatus, which allows measuring the thermal power loss of bearings by put it up on the device then provided it with the rotational motion through the electrical control panel. Reading the stability temperature of rolling bearings has done by using a thermal sensor at the speed of rotation 2000 [rpm]. The obtained results show that the thermal power loss of the Ceramic bearing is less than the Steel one. The thermal power loss with high speeds is less in the Self-aligning ball bearing comparing to the Spherical roller bearing and the Double row deep groove ball bearing. And the thermal power loss is less in the Spherical roller bearing comparing to the Double row deep groove ball bearing and that is till the approximate angular speed ω= 630 [rad/s] and after this speed the thermal power loss will increase. يعد المحمل الدحروجي من العناصر المساعدة في عمل مختلف الآليات؛ إذ يعمل كأداة ميكانيكية, تتحكم بالحركة الدورانية للأجزاء المتحركة حركة نسبية فيما بينها؛ وتتركز وظيفته في تقليل الاحتكاك والتآكل بين أعمدة الدوران, والأجسام الحاملة لها. تم في هذا البحث دراسة أنواع مختلفة من المحامل الدحروجية من ناحية تأثير كل من السرعة والحمل على أدائها, وفق منحى تجريبي عن طريق استخدام جهاز اختبار, يسمح بقياس ضياع الطاقة الحرارية في المحامل, وذلك بتركيبها على الجهاز, ثم إعطائها الحركة الدورانية بواسطة لوحة التحكم الكهربائية, وباستخدام جهاز الحساس الحراري تمت قراءة درجة حرارة الاستقرار للمحامل الدحروجية عند سرعة الدوران .2000 [rpm] أظهرت النتائج أن المحمل المصنوع من مادة السيراميك, يحصل فيه ضياعاً للطاقة الحرارية أقل بكثير من المحمل المصنوع من مادة الفولاذ. ويحصل في المحمل الكروي ذاتي المحاذاة ضياعاً أقل للطاقة الحرارية عند السرعات العالية بالمقارنة بالمحمل الدحروجي البرميلي, والمحمل الكروي ذو المجرى العميق مزدوج الصف. ويحصل في المحمل الدحروجي البرميلي ضياعاً أقل للطاقة الحرارية بالمقارنة بالمحمل الكروي ذي المجرى العميق مزدوج الصف, وذلك حتى السرعة الزاوية ω= 630 [rad/s] تقريباً, ليحصل بعد هذه السرعة ضياعاً أعلى للطاقة الحرارية.